Comparison of The Means of Argyrophilic Nucleolar Organizer Region (mAgNOR) Pre- and Post-Therapy in Nasopharyngeal Carcinoma Patients at Wahidin Sudirohusodo General Hospital Makassar - Freddy George Kuhuwael; Muhammad Fadjar Perkasa; Upik Anderiani Miskad; Abdul Qadar Punagi; Fatmawati Arsyad Said (The Prodia Education and Research Institute (PERI), 2016)
BACKGROUND: Nasopharyngeal carcinoma (NPC) is malignant tumor growing in nasopharynx with a predilection in fossa Rossenmuller and nasopharyngeal roof. This research aimed to prove whether the means of argyrophilic nucleolar organizer region (mAgNOR) can predict the success of treatment in nasopharyngeal carcinoma patients.METHODS: We used diagnostic test method with longitudinal design and purposive sampling technique. Endoscopic biopsy examination was performed on 15 nasopharyngeal carcinoma patients before and after therapy, 13 patients underwent chemotherapy and other two underwent chemoradiotherapy. Tumor tissues were stained and AgNOR was calculated.RESULTS: Based on the tumor stage, sample characteristic showed 3 patients (20%) were in stage II, 3 patients (20%) in stage III, and 9 patients (60%) in stage IV, with pre- and post-therapy mAgNOR were 1.610±0.988 and 1.000±0.000, respectively in stage II, 1.100±0.092 and 1.000±0.000, respectively in stage III, 1.226±0.265 and 1.107±0.164, respectively in stage IV patients. Based on histopathology type, 4 patients (26.7%) had non keratinizing squamous cell carcinoma with pre- and post-therapy mAgNOR were 1.117±0.134 and 1.060±0.120, respectively, while 11 patients (73.3%) had undifferentiated squamous cell carcinoma with pre- and post-therapy mAgNOR were 1.335±0.528 and 1.065±0.146, respectively. Overall the pre-therapy were significantly higher than post-therapy mAgNOR. In subgroups there are significant differences in stage IV and type 3.CONCLUSION: The values of AgNOR were decreased in all NPC stages and significantly decreased in undifferentiated squamous cell carcinoma. AgNOR can be used to predict the successfulness of therapy in NPC.KEYWORDS: nasopharyngeal carcinoma, therapy, proliferation, mAgNOR